Analytical Survey on the International Exchange of Croatian Letter Mail - Marijan Bolarić (Promet - Traffic&Transportation, 1970)
1991 was the first year of operation of the Croatian Postand Telecommunications (HPT) in the independent state ofCroatia.The public corporation HPT- Croatian Post and Telecommunicationswas established by a resolution brought by theCroatian Parliament followed by a decree pronouncing the Acton founding of the public Croatian postal and telecommunicationcorporation.This survey has studied, analysed and evaluated the internationalexchange of Croatian Letter mail with the rest of theworld from 1991-1996.